MULTICULTURALITY, PLURILINGUISM AND INTERCULTURALITY SUMMARY IN PERÚ - Huayhua Pari, Felipe (2006)
Man, culture, language and identity, the four main aspects ofmulticulturalism, pluralism and interculture help us to understand andrespect diversity, which is the environment where we live. These aspectsare developed here; each was originated in America under diversity leavingindelible traces in our history. To ignore them, would be to ignore our past,our present. This article aims at clarifying these aspects denied altogethersince Cristopher Columbus carne to America. His sucessors didn't mind these aspects, only gold and other values meantsomething to them. Civilization meant only destruction and annihilation ofthe native traits.